FOSTERING SPEAKING DEVELOPMENT AND LEARNER CONFIDENCE THROUGH DIGITAL STORYTELLING IN JUNIOR HIGH SCHOOL EFL CONTEXTS - Martha Budianto, (Journal of Innovation Research and Knowledge, 2026)
Speaking is widely recognized as one of the most essential skills in English, as it enables learners to communicate with people from different parts of the world. However, despite its importance, many students in Indonesia still experience difficulties in developing their speaking ability. These challenges are often caused by limited exposure to authentic English use, low confidence, fear of making mistakes, and a lack of engaging speaking activities in the classroom. To address this issue, this study explores the use of Digital Storytelling (DST) as an alternative instructional media used for teaching in middle-school English-speaking classes. DST allows students to combine spoken language with visuals, narration, and personal expression, creating a more meaningful and supportive environment for oral communication. This study employed qualitative approaches. Qualitative data were obtained through interviews to gain deeper insights into students’ perceptions and experiences. The findings indicate that the use of DST has a positive impact on students’ speaking ability. Not only did it improve students’ speaking performance, but it also increased their motivation to speak, enhanced their confidence, and encouraged greater creativity and self-expression. Overall, the study suggests that DST holds strong potential as an effective pedagogical tool for improving English speaking skills in the Indonesian EFL context.